Jumlah Kepala Sekolah Dan Guru Menurut Kelompok Umur Di Provinsi Lampung, Kalimantan Timur, Kalimantan Barat, Sulawesi Tenggara Tahun 2023/2024 - Khudin, Fat; Dias Saputra, Irfan; Ilham , Muhammad (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This research aims to identify the number of school principals and teachers by age group in the provinces of Lampung, East Kalimantan, West Kalimantan and Southeast Sulawesi in 2023/2024. This research uses a descriptive method to get the results and then analysis is carried out. The results show that Lampung Province has the highest number of school principals and teachers, while East Kalimantan has the lowest number. This information provides an overview of the conditions and potential needs for regeneration of teaching staff in each province. It is hoped that this data can become a reference for policy makers in designing more effective development and management strategies for teaching staff. This research also supports efforts to improve the quality of national education through sustainable human resource planning in the education sector.